If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + 4n = -6(-4 + -1n) 8 + 4n = (-4 * -6 + -1n * -6) 8 + 4n = (24 + 6n) Solving 8 + 4n = 24 + 6n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-6n' to each side of the equation. 8 + 4n + -6n = 24 + 6n + -6n Combine like terms: 4n + -6n = -2n 8 + -2n = 24 + 6n + -6n Combine like terms: 6n + -6n = 0 8 + -2n = 24 + 0 8 + -2n = 24 Add '-8' to each side of the equation. 8 + -8 + -2n = 24 + -8 Combine like terms: 8 + -8 = 0 0 + -2n = 24 + -8 -2n = 24 + -8 Combine like terms: 24 + -8 = 16 -2n = 16 Divide each side by '-2'. n = -8 Simplifying n = -8
| x^3y-4xy=0 | | 5+b= | | 2x+lne^4x=12 | | 2x+lne=12 | | (10*9+5*5)*28=x | | 4(x+2)=2(x+5) | | (10*9+5*5)=x | | 5u-7u=-8 | | 5a^2-8a-31=-10 | | 51ln(1-x)=ln(1-46x) | | (10*8+5*5)*28=x | | -28+7m=-4(4m+7) | | -1=-3/4(m+7) | | x^3-4xy=0 | | -18-11x=36 | | 100-128x=2 | | 8(x-9)=8x+-72 | | 7(6n+7)+8=-195 | | 2x-2a+b=3x+a | | -8(-5-2x)=168 | | 6x+12y-15z= | | 2(2.66)+2= | | s^2-22=112 | | -45-(-59)= | | 8=.35(c+6) | | 10-6(8x-2)=9x-(3+4x) | | 4x+2(7+6x)=142 | | 15(x+2)-1=2 | | 6x^4-16=0 | | 3(x-4)=5x+9 | | u^2-4= | | 5x+27=37 |